Pendampingan Pada Aparat dan UMKM Desa untuk Peningkatan Ekonomi Simpang Petai-Kampar - Agus Ika Putra; Enno Yuniarto; S. Siswanto; Soewignjo Agus Nugroho; Syawal Satibi; K Khairat; Syamsu Herman; Muhammad Saeri; Arisman Adnan (IKIP PGRI Bojonegoro, 2024)
Simpang Petai village was formed due to the expansion of the village in 2008. As a new village, Simpang Petai lacks facilities to face the challenges of implementing village development. The level of understanding and skills of the village officials for planning system is still very low. The participation of UMKM in the implementation of village development needs to be carried out and strengthened as one of the bases of village stability and the driving force for improving the village economy. The PkM Team of the Riau University Village Development Program, as Technical Assistance, helped solve village problems. Inventarisasi PkM team, compile activities systematically and continuously, to improve the understanding and skills of officials and village communities in the process of preparing and implementing participatory village development planning. The forming of active participation of young people, as drivers of village UMKM, in development as the basis for the resilience of rural communities and the driving force of the village economy. The activities of Advanced Welding Skills Practice, which with Product orientation, and Management Activities website Desa as the basis for village planning for Community Services and Marketing of Local Products succeeded in improving the economy of UMKM ABSTRAKDesa Simpang Petai terbentuk karena pemekaran desa tahun 2008. Sebagai desa baru, Simpang Petai minim fasilitas menghadapi tantangan melaksanakan pembangunan desa. Tingkat pemahaman dan keterampilan Aparat desa menyusun sistem perencanaan desa masih sangat rendah. Partisipasi UMKM dalam pelaksanaan pembangunan desa perlu dijalankan serta diperkuat sebagai salah satu basis stabilitas desa dan motor penggerak peningkatan Perekonomian desa. Tim Kegiatan Pengabdian Masyarakat Program Bina Desa Universitas Riau, sebagai Technical Assistance, membantu menyelesaikan permasalahan desa. Inventarisasi tim PkM, menyusun kegiatan secara sistematis dan berkesinambungan, yaitu untuk meningkatkan pemahaman dan keterampilan Aparat dan masyarakat desa pada proses penyusunan dan implementasi perencanaan pembangunan desa yang partisipatif. Terbentuknya partisipasi aktif para pemuda, sebagai penggerak UMKM desa, dalam pembangunan sebagai basis ketahanan masyarakat desa dan motor penggerak Perekonomian desa. Kegiatan Praktik Keterampilan Pengelasan Lanjut, yang dengan orientasi Produk, dan Kegiatan Pengelolaan website Desa sebagai basis perencanaan desa untuk Pelayanan Masyarakat dan Pemasaran Produk Lokal berhasil meningkatkan ekonomi UMKM.